The modification of indoor PM2.5 exposure to chronic obstructive pulmonary disease in Chinese elderly people: A meet-in-metabolite analysis. (December 2018) - Huang, Qingyu; Hu, Dayu; Wang, Xiaofei; Chen, Yahong; Wu, Yan; Pan, Lu; Li, Hongyu; Zhang, Jie; Deng, Furong; Guo, Xinbiao; Shen, Heqing
Abstract: Background: Exposure to airborne fine particulate matter (PM2.5 ) has been associated with a variety of adverse health outcomes including chronic obstructive pulmonary disease (COPD). However, the linkages between PM2.5 exposure, PM2.5 -related biomarkers, COPD-related biomarkers and COPD remain poorly elucidated. Objectives: To investigate the linkages between PM2.5 exposure and COPD outcome by using the meet-in-middle strategy based on urinary metabolic biomarkers. Methods: A cross-sectional study was designed to illustrate the mentioned quadripartite linkages. Indoor PM2.5 and its element components were assessed in 41 Chinese elderly participants including COPD patients and their healthy spouses. Metabolic biomarkers involved in PM2.5 exposure and COPD were identified by using urinary metabolomics. The associations between PM2.5 - and COPD-related biomarkers were investigated by statistics and metabolic pathway analysis. Results: Seven metabolites were screened and identified with significant correlations to PM2.5 exposure, which were majorly involved in purine and amino acid metabolism as well as glycolysis. Ten COPD-related metabolic biomarkers were identified, which suggested that amino acid metabolism, lipid and fatty acid metabolism, and glucose metabolism were disturbed in the patients. Also, PM2.5 and its many elemental components were significantly associated with COPD-related biomarkers. We observed that the two kinds of biomarkers (PM2.5 - and COPD-related) integrated in a locally connected network and the alterations of these metabolic biomarkers can biologically link PM2.5 exposure to COPD outcome. Conclusions: Our study indicated the modification of PM2.5 to COPD via both modes of action of lowering participants' antioxidation capacity and decreasing their lung energy generation; this information would be valuable for the prevention strategy of COPD. Highlights: Ambient PM2.5 exposure is associated with adverse health outcomes including COPD. The molecular linkages between PM2.5 exposure and COPD outcome remain unclear. Seven PM2.5 -related and ten COPD-related metabolic biomarkers were identified. The associations between PM2.5 - and COPD-related metabolites link PM2.5 to COPD. PM2.5 modifies COPD via lowering anti-oxidative capacity and lung energy generation.